Hubungan Pengetahuan dengan Kesiapan Wanita Menghadapi Menopause di Kecamatan Ciledug - Adin Syaefudin; Fadhila Arienda Humaira; Ahmad Nur Taufiqurrahman (Institut Nalanda, 2024)
Based on data obtained in Indonesia in 2020, the number of women living in menopause was 30.3 million. In Banten Province, the menopausal age group (40-58 years) comprised 709,476 individuals, with 163,589 in Tangerang City, 20,221 in Ciledug District, and 2,704 in Parung Serab Village. This study used a quantitative research design with a cross-sectional approach. Primary data were collected, and the sample consisted of 30 respondents. The research instrument was a questionnaire. Univariate data were analyzed descriptively, while bivariate data were analyzed using the chi-square test. Univariate results showed that 17 respondents (56.7%) were prepared for menopause, while 13 (43.3%) were not. Bivariate analysis revealed a significant relationship between knowledge and women's readiness for menopause (P-value = 0.042 <